Pengembangan Media Racing Game Tematik Sub Tema Aturan Keselamatan di Perjalanan Bagi Siswa Kelas 2 Sekolah Dasar - Rahajeng Prastiwigari; Filia Prima Artharina; Rofian Rofian (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
The purpose of this study was to determine the valid value and feasibility of developing Thematic Racing Game media as a learning medium on the Safety Themes at Home and on the Travel Themes Safety Rules in Travel for Grade 2 Elementary School students in terms of the validation of media experts, material experts, and acceptance of the media by the teacher as well as student responses. The type of research used is the Research and Development (RnD) research proposed by Borg and Gall with modifications to the initial field trials and revision of trial results based on preliminary field trial analysis including: (1) Research and information collecting, (2) Planning, (3) Developmet preliminary form a product, (4) preliminary field testing, (5) Main product revision. Data collection was carried out through interview techniques and questionnaires / questionnaires to teachers and students of grade 2 SD Negeri 1 Wanayasa and SD Negeri 3 Wanayasa, Banjarnegara Regency. The results showed that the assessment of the validation test by media experts obtained a percentage of 96.73% with very good criteria and the validation test by material experts obtained an average percentage of 94.30% with very good criteria. The results of field trials obtained a percentage of teacher acceptance of 91.18% with very good criteria and a percentage of student responses with an average acquisition of 96.52% with very good criteria.